Branchial O2 chemoreceptors in Nile tilapia Oreochromis niloticus: Control of cardiorespiratory function in response to hypoxia - Zeraik, Vivian M.; Belão, Thiago C.; Florindo, Luiz Henrique [UNESP]; Kalinin, Ana L.; Rantin, F. Tadeu (Elsevier, 2013)
This study examined the distribution and orientation of gill O2 chemoreceptors in Oreochromis niloticus and their role in cardiorespiratory responses to graded hypoxia. Intact fish, and a group with the first gill arch excised (operated), were submitted to graded hypoxia and their cardiorespiratory responses (oxygen uptake - V̇O2, breathing frequency - fR, ventilatory stroke volume - VT, gill ventilation - V̇G, O2 extraction from the ventilatory current - EO2, and heart rate - fH) were compared. Their responses to bolus injections of NaCN into the bloodstream (internal) or ventilatory water stream (external) were also determined. The V̇O2 of operated fish was significantly lower at the deepest levels of hypoxia. Neither reflex bradycardia nor ventilatory responses were completely abolished by bilateral excision of the first gill arch. EO2 of the operated group was consistently lower than the intact group. The responses to internal and external NaCN included transient decreases in fH and increases in fR and Vamp (ventilation amplitude). These cardiorespiratory responses were attenuated but not abolished in the operated group, indicating that chemoreceptors are not restricted to the first gill arch, and are sensitive to oxygen levels in both blood and water. © 2013 Elsevier Inc.
Keywords: Gill chemoreceptors; Hypoxia; Hypoxic bradycardia; Oreochromis niloticus; Ventilation; oxygen; breathing rate; cardiopulmonary function; chemoreceptor; controlled study; heart stroke volume; hypoxia; nonhuman; oxygen consumption